(untitled) (AACINI - International Journal of Industrial Engineering, 2022)
Abstract The Food and Drug Administration (FDA) proactively developed Process Analytical Technology (PAT) a few decades ago to enhance the old manner of managing analytical processes in industry. Its policy was defined as a method for developing, assessing and regulating diverging measurements of "Critical Process Parameters" (CPP) and "Critical Quality Attributes" (CQA) (CQA). Their approach has been enhanced using new tools such as "Quality by Design" (QbD) to get a thorough understanding of the production process. The spectroscopy techniques, such as near infrared spectroscopy, biosensors, Raman, fiber optic spectroscopy, and others, which have been developed with online and offline techniques to boost and improve industrial quantification of control tools such as Cp ("Process Capacity"), CpK ("Process Capacity Index"). This combination of PAT and QbD has shown to be quite effective in propelling companies into the fourth industrial revolution, in which physical and digital technologies are integrated with computer systems such as cloud and industrial internet of things (IIoT). The implementation of this new approach throughout the industry has improved the quality of the products available, resulting in higher quality, cost, and customer happiness. This vision is made feasible by the development of chemometric techniques and software that provide a better mathematical interpretation for chemical data and issues, as well as a better knowledge of production factors through multivariate linear regression. Unlike existing traditional methods, which are time-consuming and often unhealthy for the environment and humans because they use chemical reagents in their analyses, these "green" techniques take a dynamic and continuous approach, providing reliable data that is repeatable and assertive at any stage of production in which they are installed. As a result, this is a review of significant factors to consider and their general conceptualization, as well as a link between analytical chemistry, mathematics, information technologies, and manufacturing. Keywords: process analytical technology; process control; real-time monitoring, Near Infrared Tecnology, Chemometrics, FDA, Industry 4.0, Quality by Design, industrial Internet of Things, Cyber Physical Systems and Real-Time Location Systems.